Hemomucin, an O-Glycosylated Protein on Embryos of the Wasp Macrocentrus cingulum That Protects It against Encapsulation by Hemocytes of the Host Ostrinia furnacalis - Hu, Jian (J Innate Immun, 2014)
It is unclear how endoparasites passively evade their host's immune reactions in most parasite-host systems. Hemomucin from the parasitoid wasp Macrocentrus cingulum (McHEM) is a 97-kDa transmembrane protein containing 51 potential O-glycosylation sites that can be specifically recognized by Arachis hypogaea lectin. Mchem mRNA is highly expressed in M. cingulum eggs, morulae and secondary embryos, and McHEM protein is mainly located on the extraembryonic membrane of embryos. When secondary embryos of M. cingulum were transplanted into naïve larvae of their host, Ostrinia furnacalis, the embryos proliferated to generate dozens of embryos. However, more than 90% of these embryos were encapsulated by host hemocytes after blocking with anti-McHEM serum. Similarly, following knockdown of Mchem expression using double-stranded RNA encoding Mchem (dshem), many more embryos were encapsulated by host hemocytes after transplantation compared to controls (p < 0.01). Furthermore, approximately 70% of the embryos were encapsulated by host hemocytes following digestion with O-glycosidase, which specifically digests β-gal (1→3) linkages between GalNAc and Ser/Thr of proteins. Western blotting results showed that O-glycosidase digested McHEM into a smaller product. These results indicate that McHEM may protect embryos from being encapsulated by their host and that the McHEM sugar chains play an important role.